Nicotinamide N‐methyltransferase is related to MELF pattern invasion in endometrioid carcinoma - Shinichiro Tahara (Wiley, 2021)
Abstract Grade 1 (G1) endometrioid carcinoma (EC) is relatively a good prognosis. However, in a minority of cases, G1 shows an aggressive histological pattern known as the microcystic, elongated, and fragmented (MELF) pattern. We previously reported that EC with high expression levels of S100A4 and serum deprivation‐response protein (SDPR) was related to MELF pattern invasion. However, the molecular features of the invasive front area of the MELF pattern have not been investigated. In this study, we searched for genes preferentially expressed in the invasive front area of EC with the MELF pattern using laser microdissection and RNA sequencing, and showed that nicotinamide N‐methyltransferase (NNMT) is related to MELF pattern invasiveness. Immunohistochemical analyses confirmed high NNMT expression in the invasive front area of the MELF pattern. Moreover, NNMT promoted migration, invasion, colony formation, epithelial–mesenchymal transition (EMT), and chemoresistance using EC cell lines. We speculate that depletion of NNMT promotes histone methylation and leads to tumor suppression because NNMT consumes S‐adenosyl methionine (SAM), which is an essential methylation cofactor. NNMT knockout cells showed enhanced expression of H3K9me2. RNA sequencing using NNMT knockout cell lines suggested that methylation of H3K9 leads to repression of the transcription of various oncogenic genes. Our findings demonstrate the possibility that NNMT inhibitors, which are expected to be used for the treatment of metabolic disorders, would be effective for the treatment of aggressive EC. This is the first report of gene analyses focusing on the morphological changes associated with MELF pattern invasion of EC.